2004
DOI: 10.1007/s00418-003-0606-4
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase�E in rat antropyloric mucosa: distribution in progenitor and mature endocrine cell types

Abstract: Processing of most gut hormones involves cleavage between dibasic amino acids followed by carboxypeptidase-catalyzed removal of the COOH-terminal basic residue, resulting in peptides with a COOH-terminal glycine. Such peptides may subsequently be converted to amidated peptides or can be directly secreted. It is believed that carboxypeptidase E (CPE) is involved in gut hormone processing but its presence in gut endocrine cells has never been studied. We have analyzed the distribution of CPE in the antropyloric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…52 Carboxypeptidase E is a key enzyme for pro-gonadotropin-releasing hormone processing 53 and is also involved in gut hormone processing. 54 Addition of follicle-stimulating hormone to Sertoli cells increased the MMP-14 mRNA level, implicating a role in spermatogenesis. 55 Genes of C3, hormone-sensitive lipase and peroxisome proliferative-activated receptor-gamma may exert a modifying effect on lipid and glucose metabolism in familial combined hyperlipidemia.…”
Section: Resultsmentioning
confidence: 98%
“…52 Carboxypeptidase E is a key enzyme for pro-gonadotropin-releasing hormone processing 53 and is also involved in gut hormone processing. 54 Addition of follicle-stimulating hormone to Sertoli cells increased the MMP-14 mRNA level, implicating a role in spermatogenesis. 55 Genes of C3, hormone-sensitive lipase and peroxisome proliferative-activated receptor-gamma may exert a modifying effect on lipid and glucose metabolism in familial combined hyperlipidemia.…”
Section: Resultsmentioning
confidence: 98%
“…Although CPE has been detected in enteroendocrine cells of the upper GIT [14], nothing is known about CPE expression in the lower intestines. Therefore, we performed a CPE-specific staining of intestinal biopsies showing that CPE is located in defined cells of the ileal and colonic epithelium.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is increasing evidence for a CPE expression in EEC [14] implicating a functional role for EEC function and therefore for intestinal homeostasis and barrier function.…”
Section: Introductionmentioning
confidence: 99%
“…Carboxypeptidase E (CPE) is believed to be responsible for the peptide cleavage. Hougaard and Larsson (2004) studied the presence of this enzyme in the antropyloric mucosa of rat. They reported that gastrin cells and progenitor gastrin/ somatostatin cells produce CPE, whereas mature somatostatin and serotonin cells do not.…”
Section: Enteroendocrine Cellsmentioning
confidence: 99%